The value of digital 3D models in evaluating surgical outcomes using the uninjured contralateral acetabulum after acetabular fracture repair. Issue 4 (April 2023) - Nijsink, Han; Arts, Elke; Verhamme, Luc; Biert, Jan; Bemelman, Mike; Brouwers, Lars; van Wageningen, Bas
Highlights: 3D reconstructions of acetabular fractures before and after surgery were compared with reconstructions of healthy contralateral acetabula. Outcomes showed improved similarities between both acetabula after surgical reduction with low interobserver variability. Described method can potentially be used to objectively predict future arthrosis after acetabular fracture reduction. Abstract: Background: Currently, assessment of acetabular fracture reduction is mainly performed by evaluating 2D slices of 3D CT scans. This subjective method can potentially be improved by using 3D models and objective analysis tools. In order to evaluate the potential value of digital 3D reconstructed models in the assessment of acetabular fracture reduction, 3D reconstructions of the fractured acetabulum were compared to the mirrored healthy contralateral side for both the pre-, and post-surgical setting. Methods: Thirteen patients with one-sided acetabular fractures were included in the study. All patients received a pre-, and postoperative CT scan. The similarity between the healthy acetabulum and the contralateral fractured acetabulum was determined by two observers for both the pre-, and postoperative setting by completing the following four steps; (1) mirroring of the fractured acetabulum, (2) initial manual alignment of this mirrored 3D model to the contralateral version, (3) surface-based matching (iterative closest point registration) using the acetabular cartilage surface, and (4) calculating the surface distances between affected and healthy acetabular 3D models. Descriptive statistics showed the surface distance between pre-, and post-surgical reduction, as well as the interobserver variability. Results: A total of 13 patients with an acetabular fracture were included; 11 males and 2 females with a mean ± SD age of 55.6 ± 14.7 years. Digital mirroring of the fractured acetabula to the healthy acetabula was successful for both preoperative and postoperative situations in all patients. The median distance between both fractured and mirrored healthy contralateral acetabula was significantly larger ( p <0.01) for the preoperative group (2.21 mm (interquartile range (IQR): 1.30 mm)) compared to the postoperative group (0.93 mm (IQR: 0.59 mm)). The median distance deviation was not significantly different ( p  = 0.96) between observers. Conclusions: The results of comparing 3D model of fractured acetabula with the contra-lateral healthy acetabula before, and after surgical repair indicate that this method can be a suitable tool to objectively assess acetabular fracture reduction. Further research is needed to confirm the usefulness to predict future arthrosis after surgical repair.